Physiological, biochemical properties and oil degrading capacity of two sulfate - reducing bacteria strains isolated from the oil - contaminated treatment trial kheche zone, Quang Ninh province - Hoa, Tran Nhu; Cam Ha, Dang Thi (Academia Journal of Biology, 2015)
Two strains of sulfate reducing bacteria were isolated from the oil - contaminated treatment trial Kheche zone, Quangninh province and designed as KC-S1 and KC-S2. Their cells had vibrio form, with sizes 0.56-0.70 mm ´ 1.8-2.1 mm. They grew optimally at 28-37°C, NaCl 0.5-5.0% and pH 7.0-8.5. The KC-S1 and KC-S2 strains were able to degrade 14.5% and 27.4% of the oil mix (FO +DO + crude oil) respectively after 15 days of cultivation. The KC-S1 strain utilized 4.8% aliphatic hydrocarbon and 30% aromatic hydrocarbon. The KC-S2 strain utilized 10% aliphatic hydrocarbon and 22% aromatic hydrocarbon. Both strains were able to utilize n-long paraffin fractions from C35-C48.